The Gut-Brain-Microbiome Connection: Can Probiotics Decrease Anxiety and Depression?. (2nd November 2022) - Maybee, Jennifer; Pearson, Tamera; Elliott, Lydia
Abstract: Anxiety and depression are highly prevalent mood disorders worldwide. Complete remission of symptoms is often difficult to achieve, despite following recommended treatment guidelines. Numerous antidepressants and anxiolytics exist, and new drugs are being developed constantly, yet the incidence of common mood disorders continues to rise. Despite the prevalence of these issues, mental health treatment has not evolved much in recent years. An exciting area of research uncovered in the past decade is the gut-brain-microbiome axis, a bi-directional communication pathway. Because the human microbiome is closely related to mood, research is being done to investigate whether probiotic supplementation could potentially affect symptoms of anxiety and depression.